Rola pielęgniarki w wykonywaniu alergicznych testów skórnych punktowych u dzieci i dorosłych = The role of the nurse in performing skin allergy testing in children and adults - Czerwińska Pawluk, Iwona; Markut–Miotła, Ewa (Journal of Education, Health and Sport, 2015)
Czerwińska Pawluk Iwona, Markut–Miotła Ewa. Rola pielęgniarki w wykonywaniu alergicznych testów skórnych punktowych u dzieci i dorosłych = The role of the nurse in performing skin allergy testing in children and adults. Journal of Education, Health and Sport. 2015;5(1):293-304. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.44484 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A293-304 https://pbn.nauka.gov.pl/works/689296 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2015. Revised 18.01.2015. Accepted: 21.01.2015. ROLA PIELĘGNIARKI W WYKONYWANIU ALERGICZNYCH TESTÓW SKÓRNYCH PUNKTOWYCH U DZIECI I DOROSŁYCH The role of the nurse in performing skin allergy testing in children and adults Iwona Czerwińska Pawluk Uniwersytecki Szpital Dziecięcy, Lublin ul. Prof. A. Gębali 6 Radomska Szkoła Wyższa - Wydział Nauk o Zdrowiu, Radom Ewa Markut–Miotła Katedra i Zakład Pielęgniarstwa Pediatrycznego Uniwersytetu Medycznego w Lublinie Streszczenie Choroby alergiczne stanowią poważny problem współczesnej medycyny. Złożony i wieloczynnikowy ich patomechanizm jest przyczyną wielu problemów zarówno natury medycznej jak i psychospołecznych. Rozpoznanie choroby alergicznej jest podstawą wdrożenia metod terapeutycznych minimalizujących objawy choroby. W diagnostyce chorób alergicznych oprócz lekarza ważne miejsce zajmuje pielęgniarka. W ramach diagnostyki alergologicznej istotne jest przeprowadzenie wywiadu z pacjentem i/ lub jego opiekunami, badanie fizykalne, wykonanie testów alergicznych. Testy alergiczne pozwalają na identyfikację alergenu/ alergenów wyzwalających i /lub nasilających objawy chorobowe. Słowa kluczowe: choroby alergiczne, testy alergiczne. The role of the nurse in performing skin allergy testing in children and adults Abstract Allergic diseases are a serious problem of modern medicine. Complex and multifactorial patomechanism is the cause of many medical and psychosocial problems. Diagnosis of an allergic disease is the basis for implementing therapeutic methods that minimize the symptoms of the disease. In addition to the doctor’s role in the diagnostic process an important place occupies the nurse. It is important to carry out physical examination, including taking medical history of the patient and performing skin allergy testing. Skin tests enable the identification of alergen(s) triggering and/or intensifying allergic symptoms. Key words: allergic diseases, skin allergy tests.